Islamic Work Ethic as A Mediator of The Influence of Compensation and Career Development on the Employee Performance of Syaria Bank in Riau Province, Indonesia - Arie Yusnelly (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
This study aims to analyze the Islamic work ethic as a mediating effect of compensation, career development, on the performance of Islamic bank employees in Riau province. In order to face competition, Islamic banking needs to develop human resources who have skills so they can be relied on.This research uses the Structure Equation Model (SEM) by analyzing the facts that have occurred. In this study, primary data were collected using a questionnaire with a total of 288 respondents. Respondents in this study were employees of Islamic Commercial Banks in Riau Province, namely BSI, Bank Muammalat, Bank BTPN Syariah, Bank BTN Syariah, Bank Mega Syariah.This study yielded interesting findings, including the first: Compensation has a positive effect on the performance of Islamic bank employees in Riau. Furthermore, career development has a positive and significant effect on the performance of Islamic bank employees, compensation through an Islamic work ethic has a positive and significant effect on the performance of Islamic bank employees in Riau. Career Development through Islamic work ethic has no effect on the performance of Islamic bank employees in Riau.